Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau Dari Kemampuan Awal Siswa Kelas X SMAIT Anak Sholeh Mataram - Arif Fitrah Aulia; Syahrul Azmi; Ni Made Intan Kertiyani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
Mathematical problem-solving ability is a directed thinking process that students do to solve mathematical problems. This study aims to describe the mathematical problem-solving abilities of tenth-grade students at SMAIT Anak Sholeh on the topic of sequences and series, viewed from their initial ability levels (high, medium, and low). A descriptive qualitative research method was employed. Data were collected through written tests to measure initial and problem-solving abilities, and interviews to confirm student responses. The data analysis focused on the four problem-solving stages according to Polya: understanding the problem, devising a plan, carrying out the plan, and looking back. The results show a relationship between initial ability and mathematical problem-solving ability. It was found that students with high initial ability tend to have high problem-solving skills, enabling them to master all four of Polya's stages well. Students with medium ability generally faced obstacles at the planning stage, such as selecting incorrect strategies or formulas. Meanwhile, students with low ability exhibited weaknesses at every Polya's stages, starting from a poor ability to understand the problem through to re-checking the results. This study concludes that initial ability influences every stage of a student's mathematical problem-solving process, making the strengthening of initial ability an important factor to be considered for improving the quality of mathematics learning ability and students' problem-solving skills.